Social, health, and working conditions among hospital workers - Márcia Regina Alves Rocha; Maria José Sanches Marin; Juana Macias Seda; Maria Helena Borgato; Carlos Alberto Lazarini (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to compare social, health and working conditions among nursing, nutrition and hospital cleaning service workers. Methods: a quantitative cross-sectional, descriptive and correlational study carried out in a public hospital in the countryside of São Paulo, including workers from nutrition, cleaning and nursing services. Data collection occurred during working hours. Validated questionnaires and Karasek's Demand-Control model were used to assess psychosocial dimensions and the Self-Reporting Questionnaire-20 to measure the common mental disorder. As dependent variable, the groups professionals and chi-square test were used for associations with p≥ 0.05. Results: 227 workers participated. Positive associations were found between professional groups and socioeconomic, health and work characteristics. Conclusions: social, health, and working conditions differ between the professional groups studied.